Pengaruh Hamidah Rachmayanti Sebagai Co-Branding Produk Lozy Hijab Terhadap Minat Beli Konsumen - Ayu CahyanI, Regita; Yunarti, Susi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The rapid development of the Muslim fashion industry in Indonesia requires business people tocontinue to innovate in their business efforts by following trends. This study aims to determinewhether there is an influence and how much ifluence Hamidah Rachmayanti as a co-branding of LozyHijab products on consumer buying interest. The theory used is co-branding and hierarchy effects.This study uses an explanatory quantitative approach with a survey method using a questionnairedistributed to 103 respondents who are followers of the @lozyhijab Instagram account. The resultsshow that co-branding has a significant impact on purchase intention with a contribution of 88,7%,the strongest dimension of co-branding is positive consumer response, and the strongest dimension ofpurchase intention is confidence. So this study can be concluded that Hamidah Rachmayanti as cobrandinghas an effect on consumer buying interest in Lozy Hijab products.